2015
DOI: 10.1134/s1560090415040089
|View full text |Cite
|
Sign up to set email alerts
|

Micelles of amphiphilic copolymers as a medium for peroxyoxalate chemiluminescent reaction in water environment

Abstract: The peroxyoxalate chemiluminescent reaction of bis(4 nitrophenyl) oxalate or bis(pentachlo rophenyl) oxalate with hydrogen peroxide in the presence of hematoporhyrin IX water insoluble derivative in micelles or associates of Pluronics F68, L64, L61 and the alternating copolymer dimethyl siloxane ethyl ene oxide is investigated. Pluronic L61, which forms large clusters in solution, has the greatest impact on the reaction quantum yield. The micelles influence on the efficiency of the reaction with bis(pentachlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…PO-CL reaction between POX and hydrogen peroxide was performed in the presence of TMHP which participated as an activator 20 and an effective PS 1 , combining both properties. The rate of the chemiluminescence reaction was very slow (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PO-CL reaction between POX and hydrogen peroxide was performed in the presence of TMHP which participated as an activator 20 and an effective PS 1 , combining both properties. The rate of the chemiluminescence reaction was very slow (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of building blocks for polyoxalate synthesis was guided by low hydrolytic stability of oxalic esters containing electron-withdrawing substituents in phenyl fragment 20, 56 . This consideration restricted our choice to biphenols with low acidities (high pK a values).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enable in vitro and in vivo applicationsf or the detection of H 2 O 2 ,t he PO has to be protected from spontaneoush ydrolysis in aqueous media. [60] There has been av ast range of methods established in recent years to encapsulate PO-CL systems, in which the most common approachi st he enclosure of ad ye and peroxyoxalate in surfactant [61] or poly(ethylene glycol)-b-poly(e-caprolactone) [62] stabilised micelles and liposomes. [63] It has also been shown that incorporatingo xalates in polymeric materials increases their stabilityt om aket hem applicable in aqueous media.…”
Section: In Vivo Detection Of Peroxide Speciesmentioning
confidence: 99%
“…A quimiluminescência deste sistema pode ser utilizada no desenvolvimento de outros sistemas medicinais que permitam inserir ácidos nucleicos dentro de células in vivo. 70 Nos casos em que se usa o sistema peroxioxalato acoplado a cromatografia líquida e eletroforese capilar, é possível detectar compostos fluorescentes como aminoácidos, ácidos carboxílicos, compostos carbonílicos e catecolaminas, entre outros. 71 A detecção de peróxido de hidrogênio pôde ser feita em diversas condições reacionais, e também pode ser utilizada em diversos sistemas que produzem ou consomem o peróxido de hidrogênio.…”
Section: Aplicações Analíticas E Bioanalíticas Da Quimiluminescência unclassified